2022
DOI: 10.3389/fphar.2022.1014486
|View full text |Cite
|
Sign up to set email alerts
|

The median effective doses of propofol combined with two different doses of nalbuphine for adult patients during painless gastroscopy

Abstract: Objective: Propofol is the most widely administered intravenous anesthetic to induce deep sedation for gastroscopy procedures. Coadministration of nalbuphine can provide analgesia and sedation to patients experiencing visceral pain, thereby decreasing the amount of propofol needed and reducing the risk of propofol-induced adverse events. We carried out this study to determine the median effective dose (ED50) of propofol in combination with different dosages of nalbuphine and the optimal dosage of nalbuphine du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Hemodynamic fluctuations is the most frequent intraoperative adverse event in painless gastroscopy. 14 Zhan et al reported that there was no significant difference with or without esketamine administration (0.05, 0.1 and 0.2 mg/kg) in terms of hemodynamic characteristics in painless gastroscopy. 15 However, the hemodynamics were more stable as the doses of esketamine were 0.25 and 0.5 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic fluctuations is the most frequent intraoperative adverse event in painless gastroscopy. 14 Zhan et al reported that there was no significant difference with or without esketamine administration (0.05, 0.1 and 0.2 mg/kg) in terms of hemodynamic characteristics in painless gastroscopy. 15 However, the hemodynamics were more stable as the doses of esketamine were 0.25 and 0.5 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al investigated that the ED95 of nalbuphine in painless induced abortion is 0.128 mg/kg ( 20 ). While in 2022, Tang et al demonstrated that the nalbuphine dosage of 0.15 mg/kg was better than 0.1 mg/kg, as the nalbuphine dose increased from 0.1 mg/kg to 0.15 mg/kg, the ED95 of propofol in adults decreased significantly from 2.759 mg/kg to 2.243 mg/kg, with the lower incidence of hypotension and the shorter recovery time ( 21 ). Li et al concluded that the ED95 of nalbuphine combined with propofol in adults was 0.162 mg/kg ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increased satisfaction scores reflect this among patients based on their perceived quality and readiness to undergo another procedure whenever needed. It has been furtherly demonstrated that such effectiveness is usually associated with increased surgical, scientific, and clinical quality based on gastroenterologists' perspective because they can better perform upper and lower exploration procedures, which have been associated with improved adenoma resection rates and enhanced main quality indices [129][130][131][132][133]. However, besides the issues mentioned above, the effectiveness of sedation during digestive endoscopies might also be burdened by financial costs.…”
Section: Costs and Economic Issuesmentioning
confidence: 99%